Purification and characterization of recombinant thermostable T1 lipase expressed from Pichia pastoris - Periyasamy, Nalini (2015)
Thermostable lipases have high demand in various industries owing to its interesting features. Thermostable T1 lipase gene of Geobacillus zalihae was successfully cloned in Pichia pastoris. However, the characterization of purified lipase is not performed yet. Therefore, this study was conducted to determine the characteristic of the purified T1 lipase expressed in P. pastoris. The pH of the supernatant was adjusted to pH 7.4 using 1.5 M Tris-HCl and subjected to purification using Nickel-Sepharose resin. The recombinant T1 lipase was purified with 68.6 % recovery and 8.47 fold. The molecular weight of recombinant T1 lipase obtained was approximately 44 kDa. This enzyme exhibited maximum activity at temperature 70 °C and was found to be stable for two hours at 60 °C and 65 °C with relative activity of 80 % and 50 %, respectively. The optimum pH of recombinant T1 lipase was at pH 9 in 0.05 M Tris-HCl. The enzyme was found to be stable at pH 8 and pH 9 with 0.05 M Tris-HCl as its buffer. Finally, the enzyme was found to have broad substrate specificity for natural oils especially with coconut oil with 172 % relative activity. In conclusion, the recombinant T1 lipase expressed in P. pastoris was purified with the highest purification fold and its important characteristics were fully characterized.